Immune response and drug therapy based on ac4C-modified gene in pancreatic cancer typing - Xu, Dong; Huang, Kaige; Chen, Yang; Yang, Fei; Xia, Cunbing; Yang, Hongbao (Frontiers in Immunology, 2023)
N-4 cytidine acetylation (ac4C) is an epitranscriptome modification catalyzed by N-acetyltransferase 10 (NAT10) and is essential for cellular mRNA stability, rRNA biosynthesis, cell proliferation, and epithelial-mesenchymal transition (EMT). Numerous studies have confirmed the inextricable link between NAT10 and the clinical characteristics of malignancies. It is unclear, however, how NAT10 might affect pancreatic ductal adenocarcinoma. We downloaded pancreatic ductal adenocarcinoma patients from the TCGA database. We obtained the corresponding clinical data for data analysis, model construction, differential gene expression analysis, and the GEO database for external validation. We screened the published papers for NAT10-mediated ac4C modifications in 2156 genes. We confirmed that the expression levels and genomic mutation rates of NAT10 differed significantly between cancer and normal tissues. Additionally, we constructed a NAT10 prognostic model and examined immune infiltration and altered biological pathways across the models. The NAT10 isoforms identified in this study can effectively predict clinical outcomes in pancreatic cancer. Furthermore, our study showed that elevated levels of NAT10 expression correlated with cisplatin and gemcitabine resistance, that aberrant NAT10 expression may promote the angiogenic capacity of pancreatic cancer through activation of the TGF-β pathway, which in turn promotes distal metastasis of pancreatic cancer, and that NAT10 knockdown significantly inhibited the migration and clonogenic capacity of pancreatic cancer cells. In conclusion, we proposed a predictive model based on NAT10 expression levels, a non-invasive predictive approach for genomic profiling, which showed satisfactory and effective performance in predicting patients' survival outcomes and treatment response. Medicine and electronics will be combined in more interdisciplinary areas in the future.